Factors Influencing the Selection of Smartphones Among University Students: An Insight from Universiti Kuala Lumpur, Business School, Malaysia - Nurul Alyia Zamrie; Liyana Irdina Azmee; Atiqah Zainon; Mohammad Razwan Azmi; Amir Izzuddin Abd Halim (Asian Journal of Management, Entrepreneurship and Social Science, 2021)
Smartphones have become an integral part of our day to day lives. At some extent some people cannot bear without it. Meaning it is the first thing they look at when they wake up and the last thing before shutting eye. Does not matter whether it is for doing the simplest task like snapping a photo, playing a game or even bingeing on Netflix and saving documents on the cloud. Many people are now preferring the smartphone to the computer for the simplest reason of being pocket-size, easy to carry around and pretty much does the same thing a computer does. The purpose of this study is to investigate the purchase decision of Universiti Kuala Lumpur Business School students and its association with brand, price, features and social influence. The data set is collected through self-administered questionnaire. A total of 60 samples were recruited conveniently and all data collected were analyzed using SPSS software to generate the result. The findings revealed that brand, features and social influence variables were significantly influenced purchasing decision and price is found not giving any significant impact to the selection of smartphones among the university students. The finding will help marketers to understand the university consumer’s Smartphone purchase decision as well as facilitate them in developing more attractive package to influence this segment which can be considered profitable for smartphones businesses and simultaneously could boost up the sales of smartphones. The findings from this study also could enrich the existing body of literatures related to smartphones purchase decision and will be beneficials for future researchers who are having similar interest to the same field of study